Enhancing electrical discharge machining performance through employment of titanium nanopowder mixed dielectric and severe plastic deformation of electrode / Houriyeh Marashi - Houriyeh , Marashi (2016)
Electrical Discharge Machining (EDM) is one of the most promising techniques for machining high-hardness materials with geometrically complex shape, which is implemented in various industrial fields such as die and mold, aerospace and biomedical. Despite the advantages, tool wear, relatively low material removal rate and its adverse effects on surface quality limit the applications of this technique. In this thesis two techniques are employed to overcome EDM disadvantages. The first technique is the addition of powder to dielectric, namely Powder Mixed Electrical Eischarge Machining (PMEDM). The aim of this research is firstly to enhance the characteristics of AISI D2 steel surface machined with EDM through adding Ti nanopowder to dielectric under various machining parameters, including discharge duration and current. Then surface characteristics and machining productivity were investigated in terms of morphology, topography, surface cracks susceptibility and MRR. It was indicated that addition of Ti nanopowder to dielectric notably enhanced the surface morphology and surface roughness at almost all machining parameters owing to discharge dispersion. The highest improvement of around 23 and 24% in average and peak-to-valley surface roughness were attained at 1 A current and 100 μs discharge duration, respectively. Furthermore, surface elemental analysis signified negligible Ti deposition on the machined surface while the atomic concentration of Ti was increased around the crack areas. Secondly, a novel technique for enhancing EDM electrode is proposed to reduce the electrode wear in EDM, which is challenging to overcome specially when it comes to producing geometrically complex components. This technique entails a new approach for developing pure copper electrode using Severe Plastic Deformation (SPD) to enhance the machining characteristics during EDM. Equal Channel Angular Pressing (ECAP) is selected as the most popular SPD method to process EDM electrodes. The results emphasize that electrodes subjected to ECAP enhance workpiece accuracy by decreasing Volumetric Overcut (VOC) and increasing corner sharpness. It is also revealed that nanohardness enhancement following ECAP leads to lower TWR. Lastly, combination of these techniques have been employed to realize the mutual effect of these techniques, employment of Ti nanopowder mixed dielectric and ECAP treatment of electrode. It was revealed that addition of powder to dielectric in all machining conditions leads to enhancing the machined surface quality in terms of morphology and average surface roughness. In overall, ECAP treatment of electrode improve the corner sharpness of produced components, however, addition of powder to dielectric deteriorates this effect through increasing the dielectric ionization. Formation of droplets on the surface close to the cavity walls was reduced after employment of Ti nanopowder mixed dielectric or/and ECAP treatment of electrode. Furthermore, addition of powder to dielectric increase the TWR for original and ECAP-treated electrodes due to increasing the ionization of dielectric fluid and there is a negligible amount of Ti element deposited on the machined surface when employing either of electrode types.